An altered balance of plasma arginine metabolites is associated with increased thickness of the coronary intima-media complex in the adjacent to the culprit segment of an infarct-related artery. (3rd October 2022) - Molek, P; Zmudzki, P; Machnik, A; Nowak, G; Wnuk, M; Wlodarczyk, A; Nessler, J; Zalewski, J
Abstract: Background: The biomarkers of atherosclerosis remain insufficiently understood. Purpose: We sought to investigate whether an altered balance of arginine metabolites in patients following myocardial infarction (MI) is associated with remodeling of the adjacent to the culprit segments of an infarct-related artery (IRA) and with clinical outcomes. Methods: Arginine and its metabolites including ornithine, citrulline, proline and asymmetric dimethylarginine were measured using liquid chromatography and tandem mass spectrometry in 85 consecutive ST-segment elevation MI patients upon admission and at 6-month follow-up and were compared with morphology of the adjacent to the culprit proximal and distal 10-mm segments of IRA assessed with optical coherence tomography. A composite ischemic event was defined as death, recurrent MI, stroke, or unplanned percutaneous coronary intervention. Results: The ratios of citrulline/ornithine and citrulline/arginine decreased 5.22 and 2.20 times (both P<0.001) respectively, while the ornithine/arginine index (I_O/A) increased 2.96 times (P<0.001) following ischemia compared with stable follow-up, indicating the enhanced arginase activity over nitric oxide synthase (NOS) in acute phase of STEMI. Follow-up I_O/A correlated with the mean intima-media (R=0.34, P=0.003, Figure 1A) and intima (R=0.30, P=0.008) diameter of an adjacent to the culprit IRA segment. By multivariate analysis, apart from male gender (P<0.001) and diabetes mellitus (P=0.02), a higher follow-up I_O/A was associated with the larger mean intima-media diameter of an adjacent to the culprit IRA segments (coefficient 0.218, 95% confidence interval 0.040–0.397, P=0.017, per 0.01). Within the median follow-up of 25 (19–35) months, ischemic composite endpoint was found in 13 (15.3%) patients. The follow-up I_O/A reached the area under the ROC curve of 0.78 (95% confidence interval 0.66–0.91, P=0.005) for prediction of composite ischemic endpoint with a cut-off value of ≥0.57, and a sensitivity of 72.3% and specificity of 80.0% (Figure !B). Conclusions: Our findings provide arguments that during the acute phase of MI, arginine metabolism is shifted from NOS towards arginase, as compared to 6-month stable conditions. Simultaneously, the enhanced residual arginase activity over NOS in chronic phase was correlated with a higher thickness of intima or intima-media in the adjacent to the culprit segment within the IRA, and was also associated with unfavorable clinical outcomes. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Grant of the National Science Center of Poland (Number 2016/21/B/NZ5/01378 to J.Z.)